FINANCING INNOVATION ACTIVITY IN UKRAINE: REALITIES AND PERSPECTIVES - Nataliia Marynenko; Iryna Fedyshyn; Natalia Garmatiy; Iryna Kramar (Economic Review)
he role of the European Union (EU) in direct investment into the real sector of the Ukrainian economy is discussed in the article. Activity indicators of Ukrainian industrial enterprises are analyzed. Assessment of the attraction of foreign direct investment from the EU to the real sector of the Ukrainian economy is provided. The correlation between the influence of the total amount of expenditures for financing innovation activity of industrial enterprises and gross domestic product of Ukraine in actual prices is calculated and forecasting of these expenditures by applying the theory of Markov chains is carried out. The research on the basis of correlation-regression analysis between the total amount of expenditures for financing innovation activity of industrial enterprises and gross domestic product of Ukraine in actual prices for the period of 2013-2017 made it possible to establish a sufficiently strong correlation between the indicators (the correlation coefficient is 1), which indicates that the positive dynamics of the increase in the total amount of expenditures for financing innovation activity of industrial enterprises will lead to a positive dynamics of Ukraine’s gross domestic product in actual prices. This, in turn, will improve practically all indicators of the industrial activity of the national economy.